2014
DOI: 10.1186/1471-2431-14-210
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial mutation m.1555A>G as a risk factor for failed newborn hearing screening in a large cohort of preterm infants

Abstract: BackgroundThe mitochondrial m.1555A>G mutation is associated with a high rate of permanent hearing loss, if aminoglycosides are given. Preterm infants have an increased risk of permanent hearing loss and are frequently treated with aminoglycoside antibiotics.MethodsWe genotyped preterm infants with a birth weight below 1500 grams who were prospectively enrolled in a large cohort study for the m.1555A>G mutation. Treatment with aminoglycoside antibiotics in combination with mitochondrial m.1555A>G mutation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Mitochondrial DNA mutations have been linked to sensitivity to aminoglycosides and have also been associated with hearing loss in the absence of exposure to aminoglycosides [ 48 ]. Screening for genetic variants associated with hearing loss could identify patients at risk, but the opportunity for prevention may be limited as gentamicin is often prescribed on the first day of life for suspected early-onset sepsis [ 37 , 49 , 50 ]. We did not determine the prevalence of mutations predisposing for aminoglycoside toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial DNA mutations have been linked to sensitivity to aminoglycosides and have also been associated with hearing loss in the absence of exposure to aminoglycosides [ 48 ]. Screening for genetic variants associated with hearing loss could identify patients at risk, but the opportunity for prevention may be limited as gentamicin is often prescribed on the first day of life for suspected early-onset sepsis [ 37 , 49 , 50 ]. We did not determine the prevalence of mutations predisposing for aminoglycoside toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the early 1990s, a number of clinical studies have suggested that gentamicin administered in controlled therapeutic doses is not associated with ototoxicity in newborn infants [ 18 , 21 , 31 36 ]. Yet, controversies persist [ 17 , 20 , 23 , 29 , 37 ], and the dose, duration of treatment and circulating concentrations of gentamicin associated with the development of SNHL in VLBW infants have not been clearly determined.…”
Section: Introductionmentioning
confidence: 99%
“…found 10 preterm infants out of a cohort of 7056 who carried the 1555G allele and received aminoglycoside treatment, though only three of these infants failed the hearing screening. However, the combination of aminoglycoside treatment and the 1555G allele was still a significant predictor of failed newborn hearing screening, with an odds ratio of approximately 1.3 (low birth weight was the most significant predictor of a failed newborn hearing screening) [47]. Most infants who fail a newborn hearing screen do not have permanent hearing loss [47], therefore this may not be the best metric for gauging the effect of the 1555G allele on aminoglycoside-induced hearing loss.…”
Section: Important Variantsmentioning
confidence: 99%
“…and Göpel et al . note that aminoglycoside-related sensorineural hearing loss may not appear until well after the time period in which their hearing screening was performed [42, 47], a caveat that may explain the results seen in the Johnson et al . study; as mentioned earlier, previous studies have shown great variability in the length of time between aminoglycoside treatment and development of hearing loss in those with the 1555G allele.…”
Section: Important Variantsmentioning
confidence: 99%
See 1 more Smart Citation